Low background scintillation setup to investigate radiopurity of materials - Kasperovych, D.V.; Danevich, F.A.; Kobychev, V.V.; Kropivyansky, B.N.; Sokur, N.V.; Tymoshenko, A.I. (Вопросы атомной науки и техники, 2018)
Background of 2.128 kg CdWO₄ scintillation detector was reduced by 3 orders of magnitude in the energy region 0.5…2.6 MeV, and one order of magnitude above 3 MeV in the low background scintillation setup located in the basement floor of a laboratory building at the Institute for Nuclear Research (Kyiv, Ukraine). It was achieved by application of radiopure passive shield, plastic scintillators to veto cosmic rays, and pulse-shape discrimination to reject fast Cherenkov signals in the quartz light-guide of the detector. Sensitivity of the setup to radioactive contamination of different materials were estimated. For instance, for a 3.36 kg titanium sample over 30 days of measurements detection limits are on the level of 2.9 mBq/kg (⁴⁰K); 0.6 mBq/kg (¹³⁷Cs); 2 mBq/kg (²²⁶Ra), and 0.5 mBq/kg (²²⁸Th). Зниження фону низькофонової сцинтиляційної установки із сцинтиляційним кристалом CdWO₄ масою 2,128 кг складає три порядки в області енергій 0,5…2,6 МеВ і один порядок для енергій більше 3 МеВ. Придушення фону було досягнуто встановленням радіоактивно чистого пасивного захисту, пластикових сцинтиляторів для відкидання сигналів від космічних частинок і розділенням сигналів від черенковського свічення у світловоді детектора за формою. Оцінено чутливість установки до радіоактивних забруднень різних матеріалів (з довірчою ймовірністю 68%), наприклад, на рівні 2,9 мБк/кг (⁴⁰K); 0,6 мБк/кг (¹³⁷Cs); 2 мБк/кг (²²⁶Ra) і 0,5 мБк/кг (²²⁸Th) для зразку титану масою 3,36 кг протягом 30 діб вимірювання. Снижение фона низкофоновой сцинтилляционной установки со сцинтилляционным кристаллом CdWO₄ массой 2,128 кг составило три порядка в области энергий 0,5…2,6 МэВ и один порядок при энергиях больше 3 МэВ. Подавление фона было достигнуто путем установки радиоактивно чистой пассивной защиты, пластиковых сцинтилляторов для отбрасывания сигналов от космических частиц и разделением сигналов от черенковского свечения в световоде детектора по форме. Оценена чувствительность установки к радиоактивным загрязнениям разных материалов (с доверительной вероятностью 68%), например, на уровне 2,9 мБк/кг (⁴⁰K); 0,6 мБк/кг (¹³⁷Cs); 2 мБк/кг (²²⁶Ra) и 0,5 мБк/кг (²²⁸Th) для образца титана массой 3,36 кг за время измерения 30 сут.